Síntese, caracterização e comportamento térmico de amidossulfonatos de terras raras - Luiz, José Marques [UNESP]; Nunes, Ronaldo Spezia [UNESP]; Matos, Jivaldo do Rosário (Sociedade Brasileira de Química, 2013)
Hydrated compounds prepared in aqueous solution by reaction between amidosulfonic acid [H3NSO3] and suspensions of rare earth hydroxycarbonates [Ln2(OH)x(CO3)y.zH2O] were characterized by elemental analysis (% Ln, % N and % H), infrared spectroscopy (FTIR) and thermogravimetry (TG). The compounds presented the stoichiometry Ln(NH2SO3)3.xH2O (where x = 1, 5, 2.0 or 3.0). The IR spectra showed absorptions characteristic of H2O molecules and NH2SO3 groups. Degree of hydration, thermal decomposition steps and formation of stable intermediates of the type [Ln2(SO4)3] and (Ln2O2SO4), besides formation of their oxides, was determined by thermogravimetry.
Synthesis, characterization and thermal behavior of rare earth amidosulfonates
Keywords: amidosulfonates; lanthanides; thermogravimetry